Integrated experimental and computational analysis reveals amoxicillin binding dynamics to PBP1a in Staphylococcus aureus - Seifeldin Elabed; Mariam Ali; Shrouk Hanafy; Sohila Mostafa; Momen Mamdouh; Ayman Meselhi (Scientific Reports)
Abstract Methicillin-resistant Staphylococcus aureus (MRSA) represents a significant global health challenge due to acquired resistance mechanisms, primarily involving penicillin-binding protein 2a (PBP2a), necessitating novel therapeutic strategies. This study explores the potential of amoxicillin-conjugated magnetic nanoparticles (Amox-MNPs) as a means to overcome resistance by targeting the alternative essential protein, PBP1a. Fe₃O₄@SiO₂ core-shell MNPs were synthesized via controlled co-precipitation followed by a silica coating using the Stöber method, and subsequently conjugated with amoxicillin. Physicochemical characterization confirmed nanoparticle formation and successful conjugation. In vitro antibacterial assays against S. aureus ATCC 43,300 (MRSA) revealed that Amox-MNPs exhibited a mean inhibition zone diameter of 26.0 ± 0.82 mm, approximately double that of free amoxicillin (13.5 ± 1.12 mm) at equivalent concentrations (p < 0.05), indicating significantly enhanced antibacterial efficacy. Integrated computational modeling, including molecular docking and dynamics simulations, elucidated the favorable binding (−8.64 kcal/mol docking score;−32.65 kcal/mol MM-PBSA energy) and stable interaction dynamics between amoxicillin and PBP1a, identifying key stabilizing residues. These findings highlight the potential of MNP-mediated delivery to enhance amoxicillin’s efficacy against MRSA by targeting PBP1a, offering a promising preclinical strategy requiring further validation in animal models for combating resistant bacterial infections.